The sheep industry in Kansas - Birch, Raymond Russell (My University, 1906)
Introduction: A survey of the history of the sheep industry in Kansas reveals some interesting facts that are difficult to explain. At the close of the year 1872 there were according to carefully compiled statistics 39773 sheep in the state. This number gradually increased until in 1878 there were 243,760, in 1880 426492, and in 1883 the maximum number, 1,154,196 was reached. Then commenced a steady decrease in the number of sheep within the border of our state, and although the valuation of all live stock increased during the eighteen years beginning in 1883 and ending 1901, from 104 million to 155 million dollars, and the value of live stock products from 32 million to 74 million dollars, we find at the close of the year 1902 only 136,743 sheep in the state of Kansas. During the eighteen years above mentioned the number of milk cows was doubled, the number of other cattle doubled, the number of horses doubled, and the number of swine greatly increased. There were, however, only one-ninth as many sheep in the state in the year 1902 as were present in 1883. Since the year 1902 the number has begun to increase, and according to the report of 1904 there were more than 167 thousand sheep in Kansas. Since the live stock statistics of other states reveal no such fluctuation in the number of sheep as do Kansas statistics, there would seem to be some peculiarity in the conditions found in our state that renders sheep raising and sheep feeding unprofitable. Just what this peculiarity is a careful study of existing conditions fails to explain, and this leads one to the conclusion there is in reality nothing to prevent the farmers and stockmen from handling more sheep than they are now handling. Having arrived at this conclusion the reasoning followed to reach it will next be considered.
Citation: Birch, Raymond Russell. The sheep industry in Kansas. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Animal Husbandry; Sheep; Kansas; Theses